Pediatric RSV Infection During Two Winter Seasons in British Columbia: A Role for Subgroup Analysis in Young Children?. (1990) - Wilson, E; Orvell, C; Morrison, B; Thomas, E
Abstract : Using a panel of eight monoclonal antibodies directed against the G, F and NP proteins of respiratory syncytial virus, 167 virus isolates from nasopharyngeal washing cultures at British Columbia Children's Hospital during two consecutive epidemics were subgrouped. Slides made and frozen at the time of virus isolation or prepared from recovered frozen passage material, were assayed by indirect immunofluorescence. Of 85 strains tested in 1987–88, 54 (64%) were subgroup A, and 31 (36%) subgroup B. By contrast, of 82 strains tested in 1988–89 five (6%) were subgroup A and 77 (94%) subgroup B. Review of patient charts did not reveal significant differences in clinical course of patients infected with the two subgroups, but the risk of infection with subgroup A was significantly greater than the risk of subgroup B infection in younger patients.